2021
DOI: 10.1093/hmg/ddab169
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal inflammation as a link between placental expression signature of tryptophan metabolism and preterm birth

Abstract: Spontaneous preterm birth is a serious medical condition responsible for substantial perinatal morbidity and mortality. Its phenotypic characteristics, preterm labor with intact membranes (PTL) and preterm premature rupture of the membranes (PPROM), are associated with significantly increased risks of neurological and behavioral alterations in childhood and later life. Recognizing the inflammatory milieu associated with PTL and PPROM, here we examined expression signatures of placental tryptophan metabolism, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 67 publications
(76 reference statements)
0
22
0
Order By: Relevance
“…To normalize mRNA levels between different samples, we used β-2 microglobulin ( BMG ) as reference gene. The reference gene was determined based on the available literature [ 15 , 16 , 17 ]. Each sample was analyzed in two technical replications, and mean cycle threshold (CT) values were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To normalize mRNA levels between different samples, we used β-2 microglobulin ( BMG ) as reference gene. The reference gene was determined based on the available literature [ 15 , 16 , 17 ]. Each sample was analyzed in two technical replications, and mean cycle threshold (CT) values were used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Already in 1979, tryptophan concentrations were measured in the umbilical veins of term and preterm born infants [ 37 ]. The placentas of preterm pregnancies displayed an increased expression of IDO1 that was further augmented in cases of preterm premature rupture of membranes (PPROM) [ 96 ]. Other kynurenine pathway alterations included increased expression of HAAO and the transporter LAT1, but decreased expression of the enzyme KYNU, although the fold change in the latter was minimal [ 96 ].…”
Section: Pathological Pregnanciesmentioning
confidence: 99%
“…Other kynurenine pathway alterations included increased expression of HAAO and the transporter LAT1, but decreased expression of the enzyme KYNU, although the fold change in the latter was minimal [ 96 ]. IDO2 and TDO expression were unaltered [ 96 ].…”
Section: Pathological Pregnanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes involved in tryptophan metabolism/transport were highly expressed in placentas associated with sPTL. 83 Placenta RNA-seq and metabolomics studies suggest that placenta mitochondrial function and energy metabolism are altered, and the imbalanced glycolysis and unconventional lactate oxidation may be associated with sPTL. 84,85 The placenta-derived extracellular vesicles proteins proteome revealed that nonspecific inflammation coagulation was upregulated while complement activation-related proteins were downregulated in cargo from first trimester in sPTL.…”
Section: Placentamentioning
confidence: 99%